Effectiveness and cost savings of employing speech therapists in a home artificial nutrition unit - Di Battista, Alice; Di Giancaterino, Ylenia; Di Palma, Lucia; Nunziata, Claudia; Gigli, Loredana; Vivenzio, Antonio; Matano, Alessandra (Frontiers in Rehabilitation Sciences, 2025)
The Home Artificial Nutrition Unit (HANU) deals with both dysphagic patients receiving enteral and parenteral nutrition and patients who can eat orally with restrictions. In the Lazio Region, the HANU prescribes water gels and thickeners, supplied by the National Health Service (NHS), for safe hydration. Before the employment of a Speech and Language Pathologist (SLP) in the HANU (January 2023), prescriptions were standardized, regardless of the swallowing impairment severity: four jars of thickeners per patient/month and six water gels daily. The Clinical Swallowing Evaluation (CSE) made by the SLP allowed to customize the amount of thickeners and water gels based on the actual needs of the patient. The aim of this study is to investigate the cost savings resulting from the employment of an SLP in the HANU. A descriptive retrospective study was conducted, which analyzed the SLP activity in the HANU of ASL Roma 3 (January–December 2023). The study group consisted of 149 patients (61 males, 88 females with a mean age of 76.2 years) with different pathologies. The cost of each product (thickeners and gelified water) was provided by the Regional Pharmacy. The annual savings were calculated as the difference between the standardized prescription of products (as usual care in our department) and personalized prescription after SLP assessment. Since January 2023, there has been an increasing trend in requests for SLP assessments. The employment of an SLP in the HANU resulted in an annual economic saving of €30,278.67. This preliminary study shows how the employment of an SLP in the HANU can reduce inappropriate prescriptions of thickeners and water gels, thus ensuring cost savings.